Positive and negative impacts of COVID-19 in digital transformation - Subramaniam, Radhakrishnan (2021)
This study was designed to research the impact of pandemic situations such as COVID-19 in digital transformation (DT). Our proposed study was designed to research whether COVID-19 is a driver of digital transformation and to look at the three most positive and negative DT disruptors. Our study suggests that COVID-19 is a driver of digital transformation, since 94 percent of respondents agreed that COVID-19 is a driver of DT. The second phase of our study shows that technology, automation, and collaboration (TAC) is the most positive significant factor which enables work from anywhere (WFA) (or work from home) arrangements and also leads to the third positive factor of a work-life balance (WLB). The top three negative factors are no work-life balance (NWL), social employment issues (SEI), and data security and technology issues (DST). The negative factors show a contradictory result since NWL is the most negative factor, even though WLB is the third most positive factor. While the pandemic situation is leading to a positive situation for economies and organizations at a micro level, the negative impacts, which will affect overall economic growth as well as social, health, and wealth wellbeing, need to be kept in mind. The motivation of this study was to research positive and negative effects of COVID-19 on DT, since COVID-19 is impacting everyone and everyday life, including businesses. Our study developed a unique framework to address both positive and negative adoption. Our study also highlights the need for organizations and the economy to establish mitigation plans, as the pandemic has already been disrupting the entire world for the past three quarters.